Therminator DNA Polymerase: Modified Nucleotides and Unnatural Substrates - Gardner, Andrew F.; Jackson, Kiserian M.; Boyle, Madeleine M.; Buss, Jackson A.; Potapov, Vladimir; Gehring, Alexandra M.; Zatopek, Kelly M.; Corrêa Jr., Ivan R.; Ong, Jennifer L.; Jack, William E. (Frontiers in Molecular Biosciences, 2019)
A variant of 9°N DNA polymerase [Genbank ID (AAA88769.1)] with three mutations (D141A, E143A, A485L) and commercialized under the name “Therminator DNA polymerase” has the ability to incorporate a variety of modified nucleotide classes. This Review focuses on how Therminator DNA Polymerase has enabled new technologies in synthetic biology and DNA sequencing. In addition, we discuss mechanisms for increased modified nucleotide incorporation.